Сучасні погляди на діагностику та лікування пролактином - Хижняк, О. О.; Микитюк, М. Р.; Гогітідзе, Т. Г. (Clinical Endocrinology and Endocrine Surgery, 2013)
Recent trends in diagnostics and treatment of prolactinomas were reviewed. The advantages and disadvantages of surgical and pharmaceutical methods in treatment as well as the rate of radiotherapy in complex therapy of prolactinomas were discussed. High efficiency of selective agonist dopamine allows considering it as alternative to surgical treatment. The new remedies for organic hyperprolactinemia: somatostatin analogues, estrogen receptors modulators, prolactine receptor antagonists were under exploration. The ways of high dose dopamine agonists intolerance and resistance overcoming were under discussion.